Mapping the Global Research Landscape of Problem-Based Learning in Digital Learning Environments: A Bibliometric Analysis Toward Achieving SDG 4 - Hanan Zaki Alhusni; Binar Kurnia Prahani; Budi Jatmiko; Riski Ramadani; Noer Risky Ramadhani; Lindsay Natalia Bergsma; Abd. Hadi Bunyamin (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: The study aims to map the global research landscape of Problem-Based Learning (PBL) in Digital Learning Environments (DLE) using a bibliometric approach. The objective is to identify publication trends, major contributors, collaboration patterns, and emerging research themes supporting the development of sustainable digital education aligned with Sustainable Development Goal 4 (SDG 4). Method: The analysis was conducted on 2,134 documents retrieved from the Scopus database covering publications up to 2025. Data preprocessing involved duplicate removal, document filtering, and keyword harmonization. Bibliometric analysis employed performance indicators (annual publications, productive authors, sources, affiliations, and countries) and science mapping techniques (co-authorship, keyword co-occurrence, and citation analysis) using Bibliometrix and VOSviewer to visualize the intellectual structure of the field. Results: The findings reveal a substantial growth of research in this field, particularly following the global acceleration of digital education. China and the United States dominate research productivity, followed by emerging contributions from countries such as Indonesia. Publication sources are largely dominated by conference proceedings and journals in educational technology and computer science, highlighting the field's interdisciplinary nature. Novelty: This study provides a comprehensive mapping of the intellectual structure and thematic evolution of PBL research in Digital Learning Environments. It identifies research gaps, including limited international collaboration and the need for greater integration of emerging technologies such as artificial intelligence. The findings offer directions for future research to strengthen sustainable digital learning innovation and support the achievement of SDG 4.